1988
DOI: 10.1007/bf00394782
|View full text |Cite
|
Sign up to set email alerts
|

The activity of powdery-mildew haustoria after feeding the host cells with different sugars, as measured with a potentiometric cyanine dye

Abstract: Abstract. The biotrophic parasite Erysiphe graminisf. sp. hordei produces haustoria within the cells of its host Hordeum vulgare. To determine the physiological activity of these haustoria, the electric potential across the membranes in the mitochondria of the haustorium was studied. The membrane potential was estimated with the fluorescent potentiometric cyanine dye 3,3'-dibutyloxacarbocyanine iodide. The addition of depolarizing agents (carbonylcyanide m-chlorophenylhydrazone, 2,4-dinitrophenol or KCN) to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Manners (42) suggested that sucrose is the major metabolite absorbed by powdery mildew. Mendgen and Nass (43), and Aked and Hall (44), however, showed that uptake of glucose is more rapid than uptake of sucrose or fructose in powdery mildew. These data are supported by results from Sutton et al (45), indicating that glucose is the major carbon source for powdery mildew.…”
Section: Discussionmentioning
confidence: 99%
“…Manners (42) suggested that sucrose is the major metabolite absorbed by powdery mildew. Mendgen and Nass (43), and Aked and Hall (44), however, showed that uptake of glucose is more rapid than uptake of sucrose or fructose in powdery mildew. These data are supported by results from Sutton et al (45), indicating that glucose is the major carbon source for powdery mildew.…”
Section: Discussionmentioning
confidence: 99%
“…With the major plant carbohydrate transport form, sucrose, being diverted directly to the plant pathogen, it seems obvious that the pathogen should try to use this nutrient source and Manners (1989) suggested that sucrose is indeed the major metabolite absorbed by powdery mildews. However, Mendgen and Nass (1988), Aked and Hall (1993), and later Sutton et al (1999) were able to show that D-glucose is a more likely candidate carbohydrate for uptake by powdery mildew fungi. These data together with the substrate specificity determined for HXT1p in U. fabae indicate that it is not sucrose itself which seems to be utilized by the parasite.…”
Section: Rusty Power Plantsmentioning
confidence: 95%
“…In powdery mildew and rust fungi, haustoria seem to play a major role in this process (Mendgen, 1981;Woods and Gay, 1987;Mendgen and Nass, 1988;Aist and Bushnell, 1991), but the mechanism of metabolite uptake is poorly understood. Active transport of nutrients across the host-haustorial interface has been suggested.…”
mentioning
confidence: 99%